2009
DOI: 10.1098/rspb.2009.1208
|View full text |Cite
|
Sign up to set email alerts
|

Sperm length is not influenced by haploid gene expression in the flies Drosophila melanogaster and Scathophaga stercoraria

Abstract: Recent theoretical models have postulated a role for haploid-diploid conflict and for kin selection favouring sperm cooperation and altruism in the diversification and specialization of sperm form. A critical assumption of these models-that haploid gene expression contributes to variation in sperm form-has never been demonstrated and remains contentious. By quantifying within-male variation in sperm length using crosses between males and females from populations that had been subjected to divergent experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
12
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 46 publications
5
12
0
Order By: Relevance
“…In diploid organisms, despite evidence of postmeiotic gene expression in spermatozoa (e.g., Wang et al 2001; Namekawa et al 2006), sperm phenotypes appear to be determined largely by testicular, and therefore diploid, gene expression (Eddy 2002). Indeed, a recent study demonstrated that haploid gene expression does not influence sperm length variation in Drosophila melanogaster and Scathophaga stercoraria (Pitnick et al 2009b). In contrast, in the haplodiploid species studied here, the lack of a diploid phase in the male's life cycle means that selection can act exclusively on haploid genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In diploid organisms, despite evidence of postmeiotic gene expression in spermatozoa (e.g., Wang et al 2001; Namekawa et al 2006), sperm phenotypes appear to be determined largely by testicular, and therefore diploid, gene expression (Eddy 2002). Indeed, a recent study demonstrated that haploid gene expression does not influence sperm length variation in Drosophila melanogaster and Scathophaga stercoraria (Pitnick et al 2009b). In contrast, in the haplodiploid species studied here, the lack of a diploid phase in the male's life cycle means that selection can act exclusively on haploid genes.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative, not mutually exclusive, hypothesis is that variation in ejaculate traits result from genomic conflicts when the evolutionary optima for sperm traits differ between the diploid soma and its haploid sperm (Parker 1993; Parker and Begon 1993). Such haploid–diploid conflict may generate variance in sperm traits if haploid gene expression influences sperm morphology (Joseph and Kirkpatrick 2004; Immler 2008; Pizzari and Foster 2008; but see Pitnick et al 2009b). However, the extent to which ejaculate traits are shaped by haploid gene expression remains unclear (Joseph and Kirkpatrick 2004).…”
mentioning
confidence: 99%
“…This would make the effects of purifying selection associated with increased sperm competition even more powerful, especially for recessive or partially recessive variation in expression level. However, in metazoans, the scope for haploid selection appears to be relatively limited [63][64][65]. This is because DNA compaction during spermatogenesis means very few genes are expressed solely by the haploid sperm cell.…”
Section: Short-term Gene Expression Dynamics In Response To Courtshipmentioning
confidence: 99%
“…The key reason for this lack of knowledge is the current assumption that performance of sperm produced by a male is under diploid control (4-6), a notion that is further supported by the apparent lack of association between the phenotypic variation among sib sperm and their genetic content (7,8). Nevertheless, some empirical evidence shows that genes may be expressed at the haploid stages of spermatogenesis and that the transcripts of these genes are not always perfectly shared through cytoplasmic bridges among haploid spermatids (9,10).…”
mentioning
confidence: 99%